1996
DOI: 10.1021/ic951624m
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur K-Edge EXAFS Studies of Cadmium-, Zinc-, Copper-, and Silver-Rabbit Liver Metallothioneins

Abstract: The structures of metal-thiolate clusters in Zn(7)-MT, Cd(7)-MT, Cu(12)-MT, Ag(12)-MT, and Ag(17)-MT from rabbit liver have been investigated by sulfur K-edge X-ray absorption spectroscopy (XAS). In addition to providing metal-cysteinyl sulfur bond lengths, the sulfur K-edge EXAFS data provide the first direct evidence for mixtures of bridging and terminal sulfurs in Cu-MT and Ag-MT. The Zn-S and Cd-S bond lengths for tetrahedrally coordinated Zn(4)(SPh)(10)(2-) and Cd(4)(SPh)(10)(2-) compounds obtained from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 66 publications
6
43
0
Order By: Relevance
“…58 and Zn 7 -MT 58 structures, and the heterometallic rat Cd 5 Zn 2 -MT structure. 17 The metal sites in experimental protein structures are poorly determined, based on a priori fixed parameters for bonds and angles, 27,57,58 so direct comparison is made only to inorganic complexes.…”
Section: Non-strained Structures and Effect Of Screeningmentioning
confidence: 99%
“…58 and Zn 7 -MT 58 structures, and the heterometallic rat Cd 5 Zn 2 -MT structure. 17 The metal sites in experimental protein structures are poorly determined, based on a priori fixed parameters for bonds and angles, 27,57,58 so direct comparison is made only to inorganic complexes.…”
Section: Non-strained Structures and Effect Of Screeningmentioning
confidence: 99%
“…The lack of a rigid structure allows MTs to coordinate a number of metals including essential metals like zinc and copper [11], toxic metals like cadmium [12] and mercury [13], and exotic metals like uranium [14] and technetium [15]. This flexibility, while fundamental to their function, makes MTs extremely difficult to characterize structurally.…”
Section: Metallothioneinmentioning
confidence: 99%
“…However, this method can provide direct information about sulfur atom environment in proteins and metal complexes that cannot be obtained by the complementary metal K-edge measurements. The sulfur K-edge EXAFS has been applied already to inorganic materials [24][25][26][27][28][29] and metalloprotein [14,30]. However, no sulfur K-edge EXAFS studies of Zn(II) and Cd(II) complexes have been reported yet to our knowledge, in contrast, various Zn(II) and Cd(II) complexes mimicking biological systems do exist.…”
Section: Introductionmentioning
confidence: 99%